The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3892/ijo.2018.4518
|View full text |Cite
|
Sign up to set email alerts
|

Membrane proteomics of cervical cancer cell lines reveal insights on the process of cervical carcinogenesis

Abstract: The available therapeutic approaches for cervical cancer can seriously affect the fertility potential of patient; thus, there is a pressing requirement for less toxic and targeted therapies. The membrane proteome is a potential source of therapeutic targets; however, despite the significance of membrane proteins in cancer, proteomic analysis has been a challenging task due to their unique biochemical properties. The aim of the present study was to develop an efficient membrane protein enrichment protocol, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…A need for deeper understanding of the underlying mechanisms of cervical cancer pathology is critical. Towards this goal, our group has already investigated the secretome (9) and the membrane proteomes (10) of three cervical cancer cell lines in comparison to normal cervical keratinocytes with liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS). These studies highlighted the inhibition of matrix metalloproteases (9) and the deregulation of HIPPO, PI3K/Akt, and EIF2 signaling pathways (10) in cervical cancer as well as many differentially expressed proteins that are potentially crucial for cervical malignancy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A need for deeper understanding of the underlying mechanisms of cervical cancer pathology is critical. Towards this goal, our group has already investigated the secretome (9) and the membrane proteomes (10) of three cervical cancer cell lines in comparison to normal cervical keratinocytes with liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS). These studies highlighted the inhibition of matrix metalloproteases (9) and the deregulation of HIPPO, PI3K/Akt, and EIF2 signaling pathways (10) in cervical cancer as well as many differentially expressed proteins that are potentially crucial for cervical malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…Towards this goal, our group has already investigated the secretome (9) and the membrane proteomes (10) of three cervical cancer cell lines in comparison to normal cervical keratinocytes with liquid chromatography coupled with tandem mass spectrometry (LC-MS/MS). These studies highlighted the inhibition of matrix metalloproteases (9) and the deregulation of HIPPO, PI3K/Akt, and EIF2 signaling pathways (10) in cervical cancer as well as many differentially expressed proteins that are potentially crucial for cervical malignancy. Along the same lines and in an attempt to elucidate the molecular mechanisms underlining cervical carcinogenesis, we analyzed the intracellular proteome of three cervical cancer cell lines against normal cervical keratinocytes employing high resolution LC-MS/MS.…”
Section: Introductionmentioning
confidence: 99%
“…The Mann-Whitney statistical analysis used to compare the results with the non-cancer cell line HCK1T allowed them to identify 263 unique transmembrane proteins in C33, 262 unique transmembrane proteins in HeLa, and 152 unique transmembrane proteins in SiHa. Among the identified transmembrane proteins, TMX2, FAM120A, CLPTM1, CKAP5, and NCSTN were the most prominent proteins differentially expressed in CC cell lines [105].…”
Section: Proteomics and Cervical Cancermentioning
confidence: 97%
“…Another strategy for studying CC based on proteomics is the study of cell membranes as possible therapeutic targets. In 2018, Pappa et al [105] published a work on the isolation and enrichment of membrane proteins of three different cell lines, HeLa, SiHa, and C33A CC. They performed a proteomic characterization of these cell lines by LC-MS/MS and a bioinformatics analysis using Proteome Discoverer 1.4, SEQUEST, and UniProt.…”
Section: Proteomics and Cervical Cancermentioning
confidence: 99%
“…Proteomics analysis is a powerful tool for monitoring the change of protein levels to discover new biomarkers in many cancers, such as colorectal cancer, pancreatic cancer, and neuroendocrine cervical cancer ( Lin et al, 2014 ; Pan, Brentnall & Chen, 2015 ; Chauvin & Boisvert, 2018 ). Unique membrane proteins have been identified using proteomics analysis of the cervical cancer cell lines ( Pappa et al, 2018 ). Lee et al (2011) studied the proteome of cervical mucus plugs and suggested its role for maintaining pregnancy and parturition.…”
Section: Introductionmentioning
confidence: 99%